The Effect of Public Leadership and Administrative Collaboration on Hospital Performance through Employee Job Satisfaction - Natasha Waya; Dewi Wuisan (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Rapid changes in healthcare demand effective leadership and collaboration to enhance performance and service quality in hospitals. This study investigates the impact of public leadership and administrative collaboration on hospital performance, with employee job satisfaction acting as a mediating variable. The research, conducted in public hospitals in Indonesia, uses a quantitative approach with a survey method to collect data from 162 hospital employees. Structural Equation Modeling (SEM) with SmartPLS is employed for data analysis. The results show that public leadership significantly affects employee performance, while administrative collaboration strongly enhances employee job satisfaction. However, the direct impact of public leadership on employee job satisfaction is not significant, and employee job satisfaction does not significantly mediate the relationship between leadership and performance. The study also reveals that while administrative collaboration impacts employee job satisfaction, its effect on performance is not statistically significant. These findings suggest that while leadership and collaboration are vital for improving hospital outcomes, other factors should be explored to enhance performance further.